2004
DOI: 10.1111/j.0105-1873.2004.00404.x
|View full text |Cite
|
Sign up to set email alerts
|

Poor correlation between stated and found concentrations of diphenylmethane‐4,4′‐diisocyanate (4,4′‐MDI) in petrolatum patch‐test preparations

Abstract: Diphenylmethane diisocyanate (MDI) is widely used in its polymeric form in the manufacturing of polyurethane products. Previous reports on MDI-related contact allergy have shown a pattern, where patients seem to react to their own MDI-based work material but not to commercial patch-test preparations, which contain 4,4'-MDI. Therefore, we performed chemical analyses of 14 commercial test preparations of 4,4'-MDI obtained from 8 European and 4 American dermatology departments as well as 2 preparations from 2 maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 10 publications
7
57
0
1
Order By: Relevance
“…Of 179 patients with suspected occupational contact dermatitis who were investigated between 1991 and 1996 using the patch test (2% MDI in petrolatum), none reacted . One publication reports that MDI concentrations in commercial patch test preparations are often too low, so that falsenegative results in the patch tests are conceivable (Frick et al 2004). …”
Section: Skinmentioning
confidence: 99%
“…Of 179 patients with suspected occupational contact dermatitis who were investigated between 1991 and 1996 using the patch test (2% MDI in petrolatum), none reacted . One publication reports that MDI concentrations in commercial patch test preparations are often too low, so that falsenegative results in the patch tests are conceivable (Frick et al 2004). …”
Section: Skinmentioning
confidence: 99%
“…Regarding positive patch test reactions caused by MDA, it should be noted that they are relatively often seen (even in 2-4% of the patients tested), but their relevance is not always clear [28]. MDA may be used as a hardener of epoxy resins, an antioxidant of rubber products and in the production of synthetic textile fibers [13].…”
Section: Contact Dermatitis Due To Polyurethane Foam O R I G I N a L mentioning
confidence: 99%
“…Frick et al found poor correlation between the specified and true concentrations of 4,4'-MDI in petrolatum patch test preparations from 8 European and 4 American dermatology departments, which were found to contain no more than 12% of the concentrations specified in the label. The use of these preparations might have led to possible falsenegative reactions [28]. In the Finnish Institute of Occupational Medicine, an in-house test substance, containing 4,4'-MDI, MDI triisocyanate and 2,4'-MDI proved to be superior to commercial preparations of MDI [4].…”
Section: Contact Dermatitis Due To Polyurethane Foam O R I G I N a L mentioning
confidence: 99%
“…Diisocyanate, die Grundstoffe von Polyurethan-Harzen, haben nicht nur atemwegssensibilisierende, sondern auch hautsensibilisierende Eigenschaften. Aufgrund ihrer hohen Reaktivität ist ihre Stabilität in Epikutantestzubereitungen gering, sodass der Test ohne Weiteres falschnegativ ausfallen kann [20,21]. Angesichts der großen Vielfalt der möglichen beruflichen Exposition hat die DKG beschlossen, keine Testreihe für Maler und Lackierer zusammenzustellen.…”
Section: Kunststoffverarbeiterunclassified